2005
DOI: 10.1111/j.1471-0307.2005.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inulin as a fat replacer on the quality of set‐type low‐fat yogurt manufacture

Abstract: The influence of different levels of inulin on the quality of fat‐free yogurt production was investigated. Inulin was added to milk containing 0.1% of milk fat to give inulin levels of 1, 2 and 3%. The experimental yogurts were compared with control yogurt produced from whole milk. The total solids content of milk was standardized to 14% by adding skim milk powder to the experimental yogurt. The chemical composition, pH, titratable acidity, whey separation, consistency, acetaldehyde and volatile fatty acidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
160
4
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(216 citation statements)
references
References 12 publications
42
160
4
10
Order By: Relevance
“…In the whole milk formulations fermented with grains (WG), a reduction of serum separation was observed on the 28 th day of storage due to inulin addition (WGI). Fibres, such as inulin, have been reported to reduce syneresis in fermented milks during storage because of their high water holding capacity (APORTELA-PALACIOS; SOSA-MORALES; VÉLEZ-RUIZ, 2005;GUVEN et al, 2005). However, the presence of a long-chain inulin could affect the development of a 3-dimensional structure of casein resulting in a weak gel incapable of retaining water (LUCEY et al, 1998).…”
Section: Firmness and Syneresismentioning
confidence: 99%
See 1 more Smart Citation
“…In the whole milk formulations fermented with grains (WG), a reduction of serum separation was observed on the 28 th day of storage due to inulin addition (WGI). Fibres, such as inulin, have been reported to reduce syneresis in fermented milks during storage because of their high water holding capacity (APORTELA-PALACIOS; SOSA-MORALES; VÉLEZ-RUIZ, 2005;GUVEN et al, 2005). However, the presence of a long-chain inulin could affect the development of a 3-dimensional structure of casein resulting in a weak gel incapable of retaining water (LUCEY et al, 1998).…”
Section: Firmness and Syneresismentioning
confidence: 99%
“…Milk fat plays an important role in the texture development of dairy products (GUVEN et al, 2005) and reducing its concentration may cause lack of consistency or texture (EL-NAGAR et al, 2002;MAGRA;ANTONIOU;PSOMAS, 2012). Fat globules dispersed within the casein micelles interfere with protein matrix formation and resulting in the formation of a softer gel (PASEEPHOL; SMALL; SHERKAT, 2008).…”
Section: Kefir Beveragesmentioning
confidence: 99%
“…Inulin seems particularly suitable as a fat replacer in low-fat dairy products since it may contribute to an improved mouthfeel. Guggisberg et al (2009), Guven et al (2005, Kip et al (2006) and Paseephol et al (2008) showed that inulin addition to lowfat yogurt resulted in enhanced creaminess. When inulin is added to food in low concentrations, the rheological properties and the sensory quality of the product will not be affected When choosing the appropriate method of skimming, it was taken into account that the fat content (by Gerber) (Association of Official Analytical Chemists, 1998) was not higher than 0.5 g/100 mL of milk; and lipolysis was lower than 1.82 µeq FFA (Free Fatty Acids)/mL of milk since higher values may result in unwanted tastes like stale, soapy, or bitter (Deeth, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of inulin into yoghurt did not inßuence acetalde-hyde, pH and titratable acidity (Guven et al, 2005). Tyrosine and volatile fatty acidity levels were negatively affected by inulin addition.…”
Section: Effects Of Prebiotics On the Chemical Characteristic Of Yoghmentioning
confidence: 85%